Peningkatan Kapasitas Manajerial UMKM Melalui Pelatihan Manajemen Keuangan di Desa Brangjan Kec.Ungaran Barat Kab.Semarang - Umi Fadlillah Hidayanti; Wahyu Kusuma Dewi; Nyoman Sri Padmini; Gede Mandirta Tama; Salma Aprilia Hidayati; Faizah Mintya Rahmawati (STIKES Columbia Asia Medan, 2024)
This community service aims to improve the managerial capacity of Micro, Small, and Medium Enterprises (MSMEs) in Brangjan Village, West Ungaran District, Semarang Regency through financial management training. The method used is a qualitative approach with interview and observation techniques.This training covers topics such as proper financial recording, cash flow management, and budgeting to ensure business sustainability. Additionally, participants were given insights into efficient working capital management strategies and how to identify and manage financial risks commonly faced by MSMEs. The training process involved active participation from participants through case studies and group discussions, allowing them to share experiences and challenges they face in running their businesses.Based on the results of observations and interviews, most participants showed improved skills in managing their business finances, reflected in better-organized financial reports and more structured financial planning. These results indicate that the training had a positive impact on the financial and managerial performance of MSMEs in Brangjan Village. With this training, it is hoped that MSME owners in the village will be better prepared to face economic challenges, enhance competitiveness, and achieve sustainability in running their businesses.